The Role of Human Resource Development (HRD) in Optimizing Digital Services in the Banking Industry (A Study at Bank Sumsel Babel Arivai Branch) - M Daffa Rafly Asani Asani; Trisninawati (Marcha Institute, 2026)
Digital transformation in the banking industry requires organizations to not only develop technological infrastructure but also improve the competence of human resources (HR) to be able to adapt to changes in digital-based services. Bank Sumsel Babel Arivai Branch faces challenges in the form of differences in the level of technology adaptation among employees and low digital literacy among some customers who still rely on conventional services. This study aims to analyze the role of HR development in optimizing digital services at Bank Sumsel Babel Arivai Branch. The study used a qualitative descriptive method with data collection techniques through interviews, observations, and documentation studies. Research informants consisted of management, frontline employees, and related staff involved in the implementation of digital services. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the HR development program carried out through the *on-the-job training* and *off-the-job training* methods successfully improved technical competencies (*hard skills*), behavioral competencies (*soft skills*), and digital adaptability of employees. This competency improvement has an impact on optimizing digital services through increasing education on the use of the BSB Mobile, QRIS, and CRM applications for customers, accelerating the resolution of digital transaction complaints, reducing operational errors, and increasing service effectiveness. However, obstacles remain, including resistance to technology from some senior employees and low digital literacy among certain customers. Therefore, sustainable human resource development is a strategic factor in supporting the success of digital transformation and improving the quality of banking services at Bank Sumsel Babel Arivai Branch.